Revitalization of the Islamic Education Paradigm: An Islamic Epistemological Perspective - Habibi, Hasbi (Bestari, 2024)
This study seeks to investigate the concept of revitalizing the paradigm of Islamic education based in Islamic epistemology. This study employs a literature review methodology, involving the examination of data from diverse sources, including books, articles, scholarly works, and notes, to establish a theoretical foundation and gather pertinent information regarding the paradigm of education grounded in Islamic epistemology. The study's results reveal that Islamic education is predominantly dogmatic and enamored with historical aesthetics, rendering it less competitive than Western educational institutions that have successfully adapted to contemporary difficulties. Conversely, Islamic education has failed to adapt to the demands of contemporary industrial and technological civilization. In this framework, Islamic education must be a fundamental theme in the story of the future rebirth of Islamic thought. Islamic education must serve as the “core” that imbues the essence of renewal inside Islamic philosophy, enabling it to evolve and advance dynamically and gradually. Consequently, it is essential to establish a novel paradigm of Islamic education by integrating Islamic principles with modern educational concepts. This approach entails embracing contemporary education originating from the West while integrating essential principles of Islamic teachings into the revised educational framework. The epistemology of Islamic education can integrate Western philosophical epistemology with Islamic principles, as well as Islamic idealism epistemology with practical research.